THE EFFECT OF THE USE OF VISUAL COMMUNICATION MEDIA ON THE LEARNING OUTCOMES OF SPEAKING SKILLS - Kennedy, Janeru; Wiana, Rama Dwissa (STAI Darul Qalam Tangerang, 2023)
This type of research is an experiment involving one class and the form of research used is One Group Pretest – Posttest Design to find out whether or not there is an influence of the treatment given to the subject under study. The problem discussed in this thesis is whether the Influence of the Use of Visual Communication Media on Learning Outcomes of Speaking Skills in Subjects Indonesian Grade IV Students of SD Inpres Bontomanai, Tamalate District, Makassar City. The sample was grade IV students with a total of 28 students who were taken with a simple total sampling technique. The results of the analysis of learning outcomes test data show that the level of ability of grade IV students before applying the Use of Visual Communication Media to Speaking Skills Learning Outcomes in Subjects Indonesian Grade IV elementary school students are categorized as very low with a percentage of 57.14% with an average learning outcome score of 62.5. Learning outcomes after visual communication media use of speech skills learning outcomes in Indonesian subjects are categorized as high with a percentage of 92.86% and an average learning outcome score of 77.69. The results of inferential statistical analysis using the t test formula, it is known that the calculated value obtained is 8.88. With a frequency of db= 28-1 = 27, at a significant rate of 0.05% obtained tTable = 1.70. Since tCalculate > ttabel it can be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. This proves that the Effect of The Use of Visual Communication Media on Learning Outcomes of Speaking Skills in Indonesian Subjects Students are accepted